Cytogenetic and Molecular Analysis of Y Chromosome of Cryptorchid Brothers (Annals of Medical Research, 2021)
Aim: Cryptorchidism is the most frequent abnormality seen in the male reproduction system. Cryptorchidism occurs bilaterally in 10–15% of the cases. Bilateral and unilateral types of cryptorchidism are well known causes of impaired spermatogenesis. The aetiology of cryptorchidism is probably multifactorial. The patients have normal sperm production. Azoospermia factors which are responsible from the microdeletions of Y, manifest the genetic basis of cryptorchidism. The genetic aetiology of cryptorchidism has been proposed especially because of the familial repeats. The aim of this study is to determine if there is Y chromosome microdeletions in cryptorchid brothers and if there is an aetiological role of Y chromosome microdeletions in families with cryptorchidism.
Keywords: Cryptorchidism, Mutation, Chromosomal Anomaly.